2008
DOI: 10.4049/jimmunol.181.10.6829
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Antibody Therapy of Liver Metastases Reveals Functional Redundancy between FcγRI and FcγRIV

Abstract: Many patients with colorectal cancer will develop liver metastases, even after successful surgical removal of the primary tumor at a time at which no visible metastases are present. We previously demonstrated that surgery--although mandatory--paradoxically enhances the risk of developing liver metastases. Because Ab therapy has been acknowledged as a successful strategy to treat malignancies, we studied the potential of postoperative adjuvant Ab therapy to prevent outgrowth of liver metastases. Treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 53 publications
8
108
0
Order By: Relevance
“…Interestingly, blocking FcγRIV also afforded protection in model systems where FcγRIII knockout animals showed abrogation of IgG2a or IgG2b activity (20,22,23). A similar observation was made in models of antibody-mediated killing of melanoma cells, where blocking FcγRIV interfered with the activity of the therapeutic IgG2a antibody most severely on an FcγRI knockout background (14,21). Further studies in this direction are hampered by the fact that the available blocking antibody originates from hamster and becomes immunogenic after prolonged administration.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Interestingly, blocking FcγRIV also afforded protection in model systems where FcγRIII knockout animals showed abrogation of IgG2a or IgG2b activity (20,22,23). A similar observation was made in models of antibody-mediated killing of melanoma cells, where blocking FcγRIV interfered with the activity of the therapeutic IgG2a antibody most severely on an FcγRI knockout background (14,21). Further studies in this direction are hampered by the fact that the available blocking antibody originates from hamster and becomes immunogenic after prolonged administration.…”
mentioning
confidence: 74%
“…Several studies using blocking antibodies for FcγRIV indicated that this activating FcγR might play an important role for the activity of antitumor antibodies of the IgG2a and IgG2b subclass. Thus, in models of lung and liver metastases of melanoma cells and anti-CD20 antibody-dependent depletion of B cells, inhibition of FcγRIV activity resulted in the loss of the protective effects conferred by the therapeutic antibody (11,14,21). To gain further insight into the role of this receptor for the activity of anti-tumor antibodies of the IgG2a subclass, we turned to a s.c. melanoma model.…”
Section: Impact Of Fcγriv Deletion On the Expression Of Other Activatmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the dominant sources of FcγR expression in these organs are tissue-specific resident macrophages and endothelial cells. In the liver for example, Kupffer cells seem to express activating FcγRs in the spleen, red pulp macrophages are highly positive for FcγRs and thus could be involved in antibody-mediated platelet depletion [30]. In addition, strong FcγR expression can be detected on endothelial cells, although here, the dominant receptor seems to be the inhibitory FcγRIIB and probably FcγRIII to some degree.…”
Section: Effector Cells and Organs Involved In Murine (And Human) Itpmentioning
confidence: 74%
“…This in vitro binding pattern reflects the importance of the individual FcγRs for the activity of the individual IgG subclasses in different in vivo model systems. Thus, IgG1 is essentially dependent on FcγRIII, whereas IgG2a and IgG2b are additionally dependent on FcγRI and FcγRIV [24][25][26][27][28][29][30][31]. The second distinguishing feature within the family of FcγRs is whether they transduce activating or inhibitory signals.…”
Section: Introductionmentioning
confidence: 99%